Feedback between climate change and eutrophication: revisiting the allied attack concept and how to strike back. Issue 2 (3rd April 2022) - Meerhoff, Mariana; Audet, Joachim; Davidson, Thomas A.; De Meester, Luc; Hilt, Sabine; Kosten, Sarian; Liu, Zhengwen; Mazzeo, Néstor; Paerl, Hans; Scheffer, Marten; Jeppesen, Erik
ABSTRACT: Despite its well-established negative impacts on society and biodiversity, eutrophication continues to be one of the most pervasive anthropogenic influences along the freshwater to marine continuum. The interaction between eutrophication and climate change, particularly climate warming, was explicitly focused upon a decade ago by Brian Moss and others in "Allied attack: climate change and eutrophication, " which called for an integrated response to both problems, given their apparent synergy. In this review, we summarise advances in the theoretical framework and empirical research on this issue and analyse the current understanding of the major drivers and mechanisms by which climate change can enhance eutrophication, and vice versa, with a particular focus on shallow lakes. Climate change can affect nutrient loading through changes at the catchment and landscape levels by affecting hydrological patterns and fire frequency and through temperature effects on nutrient cycling. Biotic communities and their interactions can also be directly and indirectly affected by climate change, leading to an overall weakening of resilience to eutrophication impacts. Increasing empirical evidence now indicates several mechanisms by which eutrophying aquatic systems can increasingly act as important sources of greenhouse gases to the atmosphere, particularly methane. We also highlight potential feedback among eutrophication, cyanobacterial blooms, and climate change. Facing both challenges simultaneously is more pressing than ever. Meaningful and strong measures at the landscape and waterbody levels are therefore required if we are to ensure ecosystem resilience and safe water supply, conserve biodiversity, and decrease the carbon footprint of freshwaters.